PERANGARUH MEDIA KARTU KATA BERGAMBAR TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II DI SD NEGERI 21 KABUPATEN SORONG - Natalia Friskila; Desti Rahayu; Syams Kusumanigrum (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to ascertain the impact of Picture Card Media on the foundational reading abilities of Class II students at SD Negeri 21 Sorong Regency. This study employs a pre-experimental design. The study sample consisted of 14 students. The data collection instruments employed were performance tests and observations. The data analysis techniques comprise validity testing, reliability testing, normality testing, and hypothesis testing. The reliability test results yielded a Cronbach's Alpha value of 0.853, indicating a high level of reliability. The results of the Shapiro-Wilk normality test on the pretest data yielded a significance value of 0.379, which is greater than 0.05, while the posttest data yielded a significance value of 0.865, which is also greater than 0.05. The hypothesis test yielded a of 21.522 with dk = n-1 (14-1 = 13), resulting in a 2,160 sig 2 (tailed) value of 0.000. The results yielded a value of 0.000, which is less than 0.05. Therefore, the sig value is accepted and rejected, indicating that there is an influence of the use of picture-word card media on the initial reading ability of class II students at SD Negeri 21 Sorong Regency.